2017
DOI: 10.22489/cinc.2017.347-176
|View full text |Cite
|
Sign up to set email alerts
|

Can Supervised Learning Be Used to Classify Cardiac Rhythms?

Abstract: Background:This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…For a given frame the classification method must predict if the rhythm is normal, atrial fibrillation (AFib) 3 , or atrial flutter, based on the input representation. AFib is indicated by irregular RR intervals, no distinct P waves and usually variable intervals between two atrial activations (Vollmer et al, 2018). Flutter appears as a saw-tooth pattern of R waves.…”
Section: Quantitative Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…For a given frame the classification method must predict if the rhythm is normal, atrial fibrillation (AFib) 3 , or atrial flutter, based on the input representation. AFib is indicated by irregular RR intervals, no distinct P waves and usually variable intervals between two atrial activations (Vollmer et al, 2018). Flutter appears as a saw-tooth pattern of R waves.…”
Section: Quantitative Evaluationmentioning
confidence: 99%
“…It is possible that, because the Periodogram and FFT captures periodicity in the signal, it performs better than the other feature extraction methods. Work by Vollmer et al (2018) has shown that it is possible in a supervised setting. The results also shows the issues with using MLPs as a classification method for this task.…”
Section: Quantitative Evaluationmentioning
confidence: 99%
“…However, CNNs-based algorithms for stratifying cardiovascular diseases are not well-established due to limited availability of ECG database. Though a few previous studies have applied CNNs to detect cardiac arrhythmias ( Rajpurkar et al, 2017 ; Vollmer et al, 2017 ), it still remains a challenge to develop an effective algorithm for detecting AF based on short episodes of ECGs.…”
Section: Introductionmentioning
confidence: 99%
“…However, this produces a large amount of data, for which reason automated methods of AF detection are needed. The search for automated algorithms for AF detection during the PhysioNet Challenge 2017 [4] showed many promising methods, usually focused on machine learning approaches such as random forests [5], recurrent and convolutional neural networks [6], [7], supported vector machines [8] and others. However, these robust methods usually use tens or hundreds of features and may be difficult to implement in miniature processing units.…”
Section: Introductionmentioning
confidence: 99%